Associations of plasma biomarkers with cerebral perfusion and structure in Alzheimer’s disease - Yong He; Xiaojiao Liu; Fang Liu; Ping Che; Yanxin Zhang; Ruxue Fan; Yuan Li; Wen Qin; Nan Zhang (Translational Psychiatry)
Abstract Plasma biomarkers have great potential in the screening, diagnosis, and monitoring of Alzheimer’s disease (AD). However, findings on their associations with cerebral perfusion and structural changes are inconclusive. We examined both cross-sectional and longitudinal associations between plasma biomarkers and cerebral blood flow (CBF), gray matter (GM) volume, and white matter (WM) integrity. Forty-eight AD patients whose diagnosis was supported by amyloid-β (Aβ) PET received measurement of plasma biomarkers with a single molecular array, including Aβ42, phosphorylated tau 181 (P-tau181), neurofilament light (NfL), total tau (T-tau), and glial fibrillary acidic protein (GFAP), and both baseline and one-year follow-up magnetic resonance imaging, including pseudo-continuous arterial spin labeling, T1-weighted imaging, and diffusion tensor imaging. Correlations were found between regional CBF and several plasma biomarkers, with Aβ42 showing the strongest correlation with CBF in the left inferior temporal gyrus (r = 0.507, p = 0.001). Plasma P-tau181 and GFAP levels were correlated with GM volume in the posterior cingulate gyrus and the bilateral hippocampus and right middle temporal gyrus, respectively. Decreased CBF and GM volume in regions vulnerable to AD, such as the posterior cingulate gyrus, inferior parietal lobule and hippocampus, could be predicted by the levels of specific plasma biomarkers. Most biomarkers, except Aβ42, showed extensive correlations with longitudinal WM disruption. Plasma biomarkers exhibited varied correlations with brain perfusion, GM volume, and WM integrity and predicted their longitudinal changes in AD patients, suggesting their potential to reflect functional and structural changes and to monitor pathophysiological progression in the brain.